Penyuluhan Fisioterapi pada Komunitas Balita tentang Tumbuh Kembang di Posyandu Gladiol RW 12 Griya Santa, Kota Malang - Roihanah, Azzah; Sri Sunarsih Ika Wardojo; Eleonara Elsa Sucahyo (Rena Cipta Mandiri, 2025)
Toddler growth and development is an important indicator of child health, encompassing physical growth, motoric development, cognitive development, and socio-emotional development. Toddlerhood is considered the golden period, determining a child's future quality of life. Physiotherapy counseling aims to improve parents' understanding of early growth and development stimulation and the detection of developmental delays (Adnan Faris Naufal et al., 2023). This activity was conducted at the Gladiol Integrated Health Post (Posyandu) in RW 12 Griya Santa, Malang, with 21 parents of toddlers (16 mothers and 5 fathers) participating. Methods included interactive education, discussions, and demonstrations of simple stimulation for gross and fine motor skills. The results of the activity showed an increase in parents' understanding of the importance of growth monitoring (weight, height, head circumference), age-appropriate developmental stimulation, and early detection of developmental delays. This community-based counseling has positive implications for increasing parents' awareness and active role in toddler growth and development. Continuous education is needed to support the realization of a healthy and productive generation.